Targeting of Arabidopsis KNL2 to Centromeres Depends on the Conserved CENPC-k Motif in Its C Terminus. Issue 1 (6th January 2017) - Sandmann, Michael; Talbert, Paul; Demidov, Dmitri; Kuhlmann, Markus; Rutten, Twan; Conrad, Udo; Lermontova, Inna
Abstract : AtKNL2 possesses a conserved CENPC-k motif that is required for its centromeric localization and enables sequence-independent interaction with DNA in vitro but preferential binding with the centromeric repeat pAL1 in vivo. Abstract: KINETOCHORE NULL2 (KNL2) is involved in recognition of centromeres and in centromeric localization of the centromere-specific histone cenH3. Our study revealed a cenH3 nucleosome binding CENPC-k motif at the C terminus of Arabidopsis thaliana KNL2, which is conserved among a wide spectrum of eukaryotes. Centromeric localization of KNL2 is abolished by deletion of the CENPC-k motif and by mutating single conserved amino acids, but can be restored by insertion of the corresponding motif of Arabidopsis CENP-C. We showed by electrophoretic mobility shift assay that the C terminus of KNL2 binds DNA sequence-independently and interacts with the centromeric transcripts in vitro. Chromatin immunoprecipitation with anti-KNL2 antibodies indicated that in vivo KNL2 is preferentially associated with the centromeric repeat pAL1 . Complete deletion of the CENPC-k motif did not influence its ability to interact with DNA in vitro. Therefore, we suggest that KNL2 recognizes centromeric nucleosomes, similar to CENP-C, via the CENPC-k motif and binds adjoining DNA.